Comparison of the effect of ranibizumab and dexamethasone implant in diabetic macular edema with concurrent epiretinal membrane - Çakır, Akın; Erden, Burak; Aydın, Ali; Bölükbaşı, Selim; Aydın, Ali; Yurttasever Ocak, Serap; Maden, Gamze; Elçioğlu, Mustafa Nuri (Masson Editeur, 2019)
Objective. - To compare the efficacy and safety of intravitreal ranibizumab (RZB) injections and intravitreal dexamethasone (DEX) implant in diabetic macular edema (DME) with concurrent epiretinal membrane (ERM). Methods. - This was a retrospective, observational, comparative study. Medical records of DME patients with concurrent ERM were retrospectively reviewed. Seventeen eyes of 16 patients treated with 3 consecutive monthly RZB injections (RZB group) and 22 eyes of 18 patients treated with a DEX implant (DEX group) were included. The groups were compared at baseline, 1st, 2nd, 3rd and 4th months in terms of best-corrected visual acuity (BCVA), central macular thickness (CMT), and intraocular pressure (IOP). Results. - Eighteen of the 39 eyes (46.1%) were phakic at baseline, 9 (52.9%) of which were treated with RZB, whereas 9 (40.9%) were treated with DEX implant (P = 0.528). Although CMT improved significantly in both the RZB and DEX groups (P<0.001); the trend was different (P=0.003). The mean change in CMT at 1 month in the DEX group was greater (DEX: 188.2 +/- 142.7 mu m; RZB: 95.7 +/- 110.7 mu m; P=0.034); it was in favor of RZB group at the 3rd and 4th months (DEX: -52.7 +/- 86.9 mu m; RZB: 1.4 +/- 31.4 mu m; P=0.012. DEX: -63 +/- 67.3 mu m; RZB: -5.8 +/- 43.9 mu m; P=0.004, respectively). BCVA improved significantly in both groups (P < 0.001). There was no statistical difference between the groups with regard to gain in BCVA or IOP change throughout the study period (P=0.572, P=0.064, respectively). Conclusion. - Both RZB and DEX are effective in improving anatomical and visual outcomes in DME with concurrent ERM. The DEX group was associated with a prompt anatomic response, but with a gradual decrease from 3rd month.
Keywords: Ranibizumab; Dexamethasone; Epiretinal Membrane; Diabetic Macular Edema